PERCEPTION OF USURY (RIBA’) AMONG UITM DUNGUN STUDENTS: AN EXPLORATORY INVESTIGATION - Ahmad Faizal Ramly; Mohd Ariff Mohd Daud; Azarudin Bin Awang; Che Norzila Binti Sulong; Ain Nur Deeni Hassin (Journal of Islamic, Social, Economics and Development, 2022)
The public’s understanding of usury in theory or application in banks is at a low level. This lack of understanding has led to various issues arising due to misunderstandings of usury, in particular the application in Islamic Banking. As a result, more people tend to choose to use services in Conventional Banking that practice usury than Islamic Banking. This phenomenon indirectly indicates that university students who are part of society are likely to have low understanding as well. Thus, the main objective of this study is to identify the level of understanding of UiTM Dungun students on the concept of usury. This study is done quantitatively via analysis of 125 questionnaire responses from the Diploma in Muamalat, Diploma in Accounting, and Diploma in Investment Analysis students in UiTM Dungun. It was discovered that the respondents’ perceptions of usury are at an unsatisfactory level. Therefore, it is hoped that this study can contribute to the improvement of understanding, perception of UiTM Dungun students.